Analysis of the Driving Faktors for Women's Decision to Work: A Case Study of Malang City in 2024 - Aura Awalia Nawaputri; Nugroho Suryo Bintoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The socioeconomic transformation that has occurred in recent decades has brought significant changes in labor force participation patterns, particularly women's involvement in entering the labor market. This study aims to analyze the driving factors that can influence women's decisions to work in both formal and informal sectors. This research uses education level, number of children, husband's income, and marital status as independent variables. This study employs a quantitative approach with binary logit method as the estimation technique. The type of data used is secondary data from SAKERNAS (National Labor Force Survey) 2024. Based on the estimation results, it was found that education level has a high probability of influencing women's decisions to work in Malang City, while the number of children, husband's income, and marital status do not have a high probability of influencing women's decisions to work.